Chemography‐guided analysis of a reaction path network for ethylene hydrogenation with a model Wilkinson's catalyst - Gantzer, Philippe; Staub, Ruben; Harabuchi, Yu; Maeda, Satoshi; Varnek, Alexandre (Molecular informatics, 2025)
Visualization and analysis of large chemical reaction networks become rather challenging when conventional graph‐based approaches are used. As an alternative, we propose to use the chemical cartography (“chemography”) approach, describing the data distribution on a 2‐dimensional map. Here, the Generative Topographic Mapping (GTM) algorithm ‐ an advanced chemography approach ‐ has been applied to visualize the reaction path network of a simplified Wilkinson's catalyst‐catalyzed hydrogenation containing some 105 structures generated with the help of the Artificial Force Induced Reaction (AFIR) method using either Density Functional Theory or Neural Network Potential (NNP) for potential energy surface calculations. Using new atoms permutation invariant 3D descriptors for structure encoding, we've demonstrated that GTM possesses the abilities to cluster structures that share the same 2D representation, to visualize potential energy surface, to provide an insight on the reaction path exploration as a function of time and to compare reaction path networks obtained with different methods of energy assessment.